Effect of Organizational Commitment, Safety Occupational Health, on Work Discipline and Employee Performance at PT. Elnusa Petrofin Integrated Terminal Makassar - Bahauddin Ilham Rahadianto; Slamet Riyadi; Riyadi Nugroho (Indonesian Journal of Multidisciplinary Science, 2022)
Human resources have an important role in a company, therefore human resources. Humans should get special attention to knowing the indicators and get employees who are qualified to minimize the occurrence of problems or unwanted incidents within the company. Therefore, human resources are an important asset in the company, in this case, PT. Elnusa Petrofin engaged in distributing fuel oil at one price throughout Indonesia According to Hasibuan (2002: 160), employee performance is a result of work achieved by a person in carrying out his duties on skills, efforts, and opportunities. A person's commitment according to Luthans (2006:249) to the organization is one guarantee to maintain the continuity of the organization. Sinungan, (2008: 146-147) work discipline is a mental attitude that is reflected in the actions or behavior of individuals, groups, or communities in the form of compliance or obedience to the rules and regulations set. This study aims to determine the effect of organizational commitment, occupational health safety, on work discipline and employee performance at PT. Elnusa Petrofin Integrated Terminal Makassar. The data analysis technique used in this research is quantitative analysis with a sample of 162 respondents. Collecting data using a questionnaire and analyzed using SPSS to test the validity and reliability. Test the research model using SEM with the AMOS version 23 application program. The results of the study prove that organizational commitment, occupational safety, and health have a positive effect on work discipline and employee performance.